Strategi Komunikasi Samsat Pandeglang dalam Meningkatkan Kesadaran Masyarakat untuk Membayar Pajak Kendaraan Bermotor - Resa Rahmawati; Eka Susilawati; Fithrotul Kamilah; Noerma Kurnia Fajarwati; Putri Handayani (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the Samsat (Village Unit) communication strategy in improving taxpayer compliance with Motor Vehicle Tax (PKB) in Pandeglang Regency. The study employed a qualitative approach, with data collection techniques including in-depth interviews, non-participant observation, and documentation studies. Informants were selected purposively, including internal Samsat personnel (heads of technical implementation units, socialization officers, social media administrators, Mobile Samsat coordinators, and the Regional Revenue Agency) and the public (compliant taxpayers, delinquent taxpayers, and community leaders). Data analysis was conducted using an interactive model through reduction, presentation, and drawing conclusions through source triangulation. The results indicate that communication strategies through direct outreach, social media, Mobile Samsat services, and the Tax Amnesty Program have proven effective in increasing taxpayer participation and compliance. The amnesty program, in particular, is effective in attracting delinquent taxpayers and has an impact on increasing regional revenue. This study concludes that an appropriate, consistent, and community-based communication strategy plays a crucial role in optimizing PKB revenue. These findings can serve as a reference for formulating more innovative and sustainable communication strategies to increase Regional Original Income (PAD).